Protective effect of bioactive peptide carnosine against lead-induced oxidative stress in kidney of rats - Hasanein, P; Teimuri-Far, M (Cellular and Molecular Biology, 2015)
Oxidative stress is among the mechanisms involved in renal injury. We aimed to investigate the protective effects of bioactive peptide carnosine on lead induced oxidative stress and nephrotoxicity in rats. Animals received an aqueous solution of lead acetate (500 mg Pb/L in the drinking water) and/or carnosine (10 mg/kg, i.g.) for eight weeks. Then rats were weighed and used for biochemical, histological and oxidant/antioxidant evaluations. Lead-induced oxidative stress in renal tissue was indicated by a significant increase in the renal contents of malondialdehyde (MDA) as well as decrease in the levels of reduced glutathione (GSH), total antioxidant capacity (TAC), catalase (CAT) and superoxide dismutase (SOD) (P’s < 0.001). Carnosine treatment decreased MDA whereas it increased the contents of GSH, TAC, CAT and SOD in both lead and control groups. Carnosine prevented the increased kidney weight and lead-induced deleterious effects on serum creatinine, urea, uric acid, albumin and total protein in lead group. It also attenuated lead induced abnormal renal structure. The present study showed that carnosine protected against lead induced oxidative stress and renal injury in rat. Therefore, carnosine represents a potential therapeutic option against the deleterious effect of lead induced nephrotoxicity which deserves consideration and further examination.